Pengembangan Perangkat Pembelajaran IPA Fisika Melalui Model Pembelajaran Inkuiri Dengan Metode Pictorial Riddle - Imelda, Imelda; Jamal, M. Arifuddin; Suyidno, Suyidno (Universitas Lambung Mangkurat, 2013)
Learning device in SMP Negeri 4 Banjarmasin has not been designed to accommodate the needs of students to actively learn and solve problems on their own during the learning process, therefore carried out a study aimed at describing the effectiveness of the development of the physical science learning through inquiry learning model with the method of pictorial riddle. In particular, this study aimed to describe: (1) the feasibility study, (2) lesson plan implementation, (3) students critical thinking skills, (4) learning outcomes, (5) the response of students towards learning. This refers development research to the Dick and Carey. Data retrieval techniques through achievement test, observation, questionnaires, and documentation. The results were analyzed by descriptive qualitative and quantitative. The results showed that: (1) a device developed includes lesson plans, Teaching Materials and LKS are reliable instrument used, (2) the method of inquiry learning lesson plan implementation of using pictorial riddle methods in good category. (3) students critical thinking skills that include known issues, define hypotheses, solve problems, collect data, evaluate, and conclude are in good category. (4) learning outcomes that indicates with classical TPK completeness in good category is achieved with good overall sensitivity and sensitive, although there is a small unfinished because of the difficulty in analyzing the problem, (5) The students response of to the inquiry learning model with pictorial riddle methods is in good category. Retrieved conclusion that the physical science device which is developed are effective to improve critical thinking are students and learning outcomes learning through inquiry learning model with pictorial riddle methods.Â